Neuroprotective action of bacterial melanin in rats after corticospinal tract lesions - Petrosyan, Tigran R.; Gevorkyan, Olga V.; Meliksetyan, Irina B.; Hovsepyan, Anna S.; Manvelyan, Levon R. (Pathophysiology (Amsterdam), 2012)
► Four groups of rats were subjected to unilateral pyramidotomy. ► Part of the rats was injected with melanin after transection of the motor tract. ► Behavioral, electrophysiological and histomorphological experiments were conducted. ► Motor recovery was faster in rats treated with bacterial melanin. ► Results show recovery of corticospinal conductivity in rats treated with melanin. Experiments were performed on 48 albino rats. Part of the experimental animals were initially trained to a balancing instrumental conditioned reflex (ICR). Unilateral bulbar pyramidotomy performed in all rats caused contralateral hemiparesis. On the next day following the operation 24 rats were injected intramuscularly with bacterial melanin solution. 12 of these rats were initially trained to ICR. Recovery periods of ICR and paralyzed hindlimb movements were registered for melanin injected rats (n=24) and for operated rats, not treated with melanin (n=24). In rats injected with bacterial melanin the posttraumatic recovery is shorter than in animals not treated with melanin. The fastest and complete recovery was registered in rats initially trained to ICR and injected after the operation with bacterial melanin. Electrophysiological experiments were performed in transected animals treated with melanin, transected animals without melanin treatment and intact animals. Spiking activity of motoneurons was registered in lumbar motoneurons of rats in response to high frequency stimulation above the corticospinal tract transection. Spiking activity was very similar in motoneurons of melanin injected and intact or non operated animals. In animals, not dosed with bacterial melanin after the operation, areactivity or no change in firing rate was registered in response to stimulus. Stimulation of the corticospinal tract of melanin injected rats produced potentiation of the motoneuronal firing rate and is an evidence of regeneration in corticospinal tract. Similarity in spiking activity of intact and melanin injected rats shows the recovery of conductance in pyramidal tract. Morphohistochemical examination was carried out to confirm the results of behavioral and electrophysiological experiments. Medulla slices were prepared to trace the regeneration of nerve fibers. Examination of transection area revealed that bacterial melanin increases vascularization, dilates the capillaries in nervous tissue and stimulates the process of sprouting.